Twin spica. 9 - Yaginuma, Kō, 1973- (Vertical, Inc., 2011)
Twin Spica, Asumi and her classmates are getting closer and closer towards graduation and the competition is getting fierce. There are some changes in store for this group of friends. There will be good-byes to be said and that might end up causing some difficulty within this group. Some of that might be spurred on from outside of the Tokyo Space School as the media has caught on to the identities of at least one prime candidate.